Structural investigations oof rapidly quenched Nb-0-50at.%Co alloys - Schlüter H.; Sastry G.V.S.; Freyhardt H.C. (My University, 2025)
NbCo alloys quenched at different cooling rates (Ṫ ranging from 105 to 108 K s-1) are investigated by X-ray diffraction and transmission electron microscopy. A metastable extension of the b.c.c. solid solution up to 26 at.% Co can be achieved by using quenching rates of the order of T ̇ = 107 K s-1. According to electron diffraction observation the metastable solid solution decomposes into an α-solid solution with low cobalt content and an amorphous cobalt-rich phase upon annealing at about 830 K for cobalt concentrations less than 20 at.%. When annealed at higher temperatures, the metastable solid solution returns to equilibrium constitution through an intermediate stage of formation into a CsCl-type phase or one related to μ phase. Between 26 and 50 at.% Co, the alloys are directly quenched into the amorphous state at the highest cooling rate. The occurrence of a split maximum in high concentration amorphous alloys and role of quenching stresses in the formation of an amorphous phase with low cobalt concentration are also discussed. © 1988.